The The Phenomenon of Non-Medical Assistance in Childbirth in the Work Area of UPT Community Health Center Palangkau - Haryono, Ika Avrilina; Marsela, Mira; Salmarini, Desilestia Dwi (Journal Of Health Science (Jurnal Ilmu Kesehatan), 2024)
The assistance of midwives in childbirth is one of the strategies related to maternal and child health issues. In Indonesia, the utilization of midwifery assistance in the community is still low compared to the expected indicators. According to data from Palangkau Community Health Center in 2022, there were 7 mothers assisted by non-medical personnel during childbirth. Several factors influence the choice of childbirth assistance, including the distance to health facilities, transportation, trust, costs, and others. The aim of this research is to describe the phenomenon of childbirth assistance by non-medical personnel in the work area of UPT Community Health Center Palangkau. It is a descriptive study with a qualitative approach. The main informants are 10 mothers who gave birth with the assistance of traditional birth attendants from 2022 to 2023. The research results indicate that all mothers prefer and utilize assistance from traditional birth attendants due to the strong community trust in them, as well as the generational aspect. Other influencing factors include the cost of childbirth, the distant location of health facilities, inactive health insurance, and issues related to still having to pay for childbirth even with health insurance, as well as inadequate transportation. Therefore, health policy solutions and interventions need to be holistic, considering various factors influencing community decisions. This poses a significant challenge in achieving optimal maternal health while highlighting potential opportunities to enhance childbirth services and strengthen maternal health systems.